(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
Preliminary study to measure gaseous ozone concentration using ultraviolet absorption spectroscopy is presented. Firstly, background of ozone is introduced. Next, fundamental theory behind ultraviolet absorption spectroscopy is discussed based on Beer-Lambertâ€™s Law and absorption spectrum of ozone. After that, absorption cross section of ozone is simulated via spectralcalc.com. Temperature of system is varied. Peak absorption cross section and peak absorption wavelength are found to be 1.166 Â´ 10-21 m2 molecule-1 and 255.376 nm respectively at 300 K and 0 torr. Absorption cross section in ultraviolet region shows slight variation of at most 1.286 per cent when temperature is changed from 200 K to 300 K. Around room temperature, peak absorption cross section simulated in current work is consistent with previous work, because relative error is found to be small in between 1.630 per cent and 3.087 per cent. Unlike previous work, absorption of light by ozone is detected in ultraviolet region only due to weak absorption in visible region.